INCIDENCE AND RISK FACTORS FOR SCAR DEHISCENCE IN LOWER SEGMENT CESAREAN SECTION - Akbar, Amina; Zaineb, Sadia; Mahboob, Saira; Khan, Samra (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the incidence and risk factor for scar dehiscence in parturient with previous LSCS.Study Design: Prospective, observational study.Place and Duration of Study: Department of Gynecology and Obstetrics; department of Anesthesiology, Combined Military Hospital, Okara, from Jul to Dec 2018.Methodology: After the approval of hospital ethical committee, 300 parturient undergoing cesarean section were included in our study. The outcomes were incidence and risk factors for scar dehiscence. SPSS version 20 was used to analyze data. Descriptive data was presented as frequency and percentage. Chi square was used to calculate significance and p-value less than 0.05 taken as significant.Results: A total of 300 patients with previous cesarean delivery were included in our study. Our study has shown that no use of antepartum nutritional supplement (30.3% vs 66.7%), early term pregnancy, emergency LSCS (40.9% vs 8.1%), laboring patient (30.3% vs 4.7%) with duration of labor more than 24 hours (3% vs 0.9%) and inter-delivery gap (2.01years ± 1.05 vs 2.3 years ± 0.96) are independent risk factors for scar dehiscence in patient with history of previous cesarean sections, p-value